ANALYSIS OF SINGLE SLOPE GEOMETRY ON THE LOWWALL SLOPES OF PT XYZ COAL MINING - Try Saputra, Dyoh
In open-pit coal mines with a steep coal seam, the stability of the lowwall slope will always be controlled by the presence of a bedding plane. Therefore, the presence of bedding planes in rock during excavation activities need to be considered carefully. In this study, a model of a single slope in the lowwall slope which considering the actual situation is made, and then its stability considering the slip plane through the bedding plane is calculated by the simplified Janbu method using Slide 6.0 software. The single slope model with variations in its slope height is also created for the purpose of understanding the effects of slope height. Assuming a vibration load of 0.05g, the minimum flat distance between the weak plane and the slope crest that provides the safety factor greater than or equal to 1.1 is sought. The results of the study can be given as follows : for a slope height given of (m) 10 ; 15; 20; 25; 30; 40; 50, then the minimum flat distance of the weak plane to the crest of safe slope is successively (m) 7 ; 13 ; 20 ; 29 ; 35 ; 50 ; 63.. It is necessary to handle the groundwater level properly so that the minimum flat distance obtained can be smaller, however, the slope height can be maintained high, so that coal recovery is getting better.